Immediate Delivery Versus Expectant Monitoring for Hypertensive Disorders of Pregnancy Between 34 and 37 Weeks of Gestation (HYPITAT-II): An Open-label, Randomized-Controlled Trial. Issue 2 (June 2016) - Broekhuijsen, K.; van Baaren, G.J.; van Pampus, M.G.; Ganzevoort, W.; Sikkema, J.M.; Woiski, M.D.; Oudijk, M.A.; Bloemenkamp, K.W.; Scheepers, H.C.; Bremer, H.A.; Rijnders, R.J.; van Loon, A.J.; et al.
Abstract : ( Lancet. 2015;385(9986):2492–2501) Hypertensive disorders of pregnancy occur in approximately 10% of all pregnancies. Although the first Hypertension and Preeclampsia Intervention Trial At Term (HYPITAT) study demonstrated that immediate delivery reduces the risk of adverse maternal outcomes for women with mild gestational hypertension or preeclampsia past 37 weeks of gestation, little is known about the risks and benefits of immediate delivery versus continuing the pregnancy for women at 34 to 37 weeks of gestation who have hypertensive disorders. This open-label, randomized-controlled trial investigated the effect of immediate delivery versus expectant management on maternal and neonatal outcomes for women with hypertensive disorders at 34 to 37 weeks' gestation.